Agama dan Diplomasi Publik: Peran Nahdlatul Ulama (NU) dalam Agenda Perdamaian Indonesia - Afghanistan - Emharis Gigih Pratama; Ferdiyan (IAIN Pekalongan, 2021)
This research aims to analyze the role of Nahdlatul Ulama (NU) in succeeding the Indonesian’s public diplomacy through peace agenda for Afghanistan. Cooperation and partnership between Indonesia and Afghanistan entered a new phase with a focus on the conflict reconciliation and capacity building agendas. Indonesia becomes Afghanistan's top choice to become a peace broker between the Afghan government and the Taliban, since no assistance has been offered by other Muslim countries and the Indonesian’s property of Islamic ‘Wasathiyah’ diplomacy has been attractive. Thus, this research will answer why is NU more favorable than its similar moderate organization, Muhammadiyah, and what are the main roles of NU in supporting the government’s agenda. By using interview and collecting secondary data and implementing soft power theory framework, multitrack diplomacy, and public diplomacy, this study found that there are three important roles hold by NU in this case. First, NU as an actor who has credibility in the field of Islamic Wasathiyah discourse, second, NU acts as a strategic collaborative partner of the Indonesian government by engaging in several official state programs, and third, NU carries out its public diplomacy role by initiating independent programs for Afghanistan.